Avaliação de manifestações patológicas por técnicas não destrutivas (NDT): inspeções nas pontes rurais no município de Alegre - ES - Santos, Daniel Ader da Silva (2023)
In any structural project of a wooden bridge, it is necessary to know the type of material that is being used in its construction or for its maintenance, whether preventive or corrective. This knowledge is important, because it is through it that the type of technology and equipment to be used for an analysis, both physical and mechanical, is determined in order to obtain the sanity of the structural parts. Corroborating a considerable reduction in corrective maintenance, due to the efficiency in the use of visual inspection, resistography and ultrasound as allied to preventive maintenance. Among numerous methods used in already built and large wooden structures, the methods of analysis of resistance to penetration by means of the resistograph and the ultrasonography using ultrasound stand out, these methods, which do not require the removal of the piece from the site to carry out the analysis. Both the resistograph and the ultrasound are equipment of simple application and of great efficiency for mechanical and physical analysis in a wooden structure, making it possible to determine the resistance and quality of the structural part under study, avoiding its replacement or unexpected rupture. In the southern region of the state of Espírito Santo, more precisely in the municipality of Alegre and its districts, there is a large number of wooden bridges in full use, but most of them are in a critical state of conservation due to the lack of analysis in preventive maintenance. This fact, which collaborates for the most part, in corrective maintenance, which in turn, generates public expenses and harms rural producers who need bridges to transport their production, in addition to insecurity in school transport and other people who make use of such structures for their development.